Indonesian pediatricians’ understanding and management of infant regurgitation based on Rome IV criteria - Fransesco Bernado Hubert Jonathan; Agus T. Sridevi; Brahmantyo A. Wicaksono; Dewi Friska; Badriul Hegar (Indonesian Pediatric Society, 2022)
Background The diagnostic criteria of infant regurgitation have been well elucidated in the Rome IV criteria and pediatricians have been informed of them. However, as a functional disorder, infant regurgitation is susceptible to misdiagnosis and inappropriate management. Objective To assess pediatricians’ diagnostic knowledge of and therapeutic approach to infant regurgitation. Methods We conducted a cross-sectional, analytical study using a questionnaire based on Rome IV criteria for infant regurgitation diagnosis and standardized guidelines for management. The questionnaire was face-level validated by an expert and tested for both reliability and correlation using 30 test respondents. The questionnaire was then distributed electronically to 131 randomized pediatricians, who were members of the Indonesian Pediatric Society DKI Jakarta branch and graduated from pediatric residency within year 2005-2019. Results Sixty-seven (51%) pediatricians reported applying the Rome IV criteria in daily clinical practice. Pediatricians who used Rome IV as their source of knowledge achieved mean and median diagnostic knowledge scores of 14.87 (SD 2.540) and 16 (range 8–20), respectively, with no significant correlation between the usage of ROME IV and the pediatricians’ diagnostic understanding (P=0.110), and mean and median therapeutic knowledge scores of 9.10 (SD 2.264) and 10 (range 4–12), respectively, with no significant correlation between the usage of ROME IV and the pediatricians’ therapeutic approach (P=0.486). Pediatricians’ diagnostic knowledge and therapeutic approach were not significantly different with regards to their practice experience, specialist institution, workplaces, and source of information. Conclusion The majority of pediatricians surveyed have good diagnostic and therapeutic knowledge scores with regards to handling of Rome IV infant regurgitation.